In vitro determination of the antibacterial effect of honey bee (Apis mellifera) and little angel bee (Tetragonisca angustula) against positive coagulase Staphylococcus aureus (Revista Sistemas de Producción Agroecológicos, 2013)
The indiscriminate misuse of antibiotics in recent decades, for prophylaxis of diseases in man and animals, has triggered an alarm in the world of medicine microbiological, since these microorganisms have responded in a dangerous way, with called bacterial resistance, so it is necessary to recognize, investigate and apply in our professional field, there are alternative options in veterinary medicine. The objectives in the present study are to establish if the honey bee Apis mellifera (honeybee) and honey bee Tetragonisca angustula (angelita or virgin bee) obtained from our regional flora, possess some antibacterial feature inhibit microbial growth achieved in different bacterial concentrations planting, later analyze and compare them statistically. The results obtained were asked comparative and descriptive analysis of the population mean, using this program estad.graphad.instat Software version 3.06 (2003). It looked for statistically significant differences between pairs P
Keywords: bacterial resistance; antibacterial; minimum inhibitory concentration; honey